2020
DOI: 10.1111/jocn.15406
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the factors influencing career choice in mental health

Abstract: Aims and objectives To identify the factors that are associated with considering a career in mental health. Background The mental health specialty is facing a recruitment crisis in the United Kingdom but there is limited evidence about which factors encourage and discourage people from considering a career in mental health. Design Quantitative, observational, online survey using a multiple ordinal logistic regression model to identify if there were any significant predictors of the extent to which participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Students who spend more time (more than a month) doing their psychiatry ward rotation are more likely to develop interest in mental health than those who spend less time (not more than a month or no psychiatry rotation) [12]. A greater knowledge of mental health, better perception of job prospects in psychiatric nursing than other fields, and having a positive attitude towards psychiatry are also linked to choosing a career in mental health nursing [14,15]. Apart from the direct influence of stigma towards people with mental illness, the exposure of students considering a career in mental health to stigmatizing comments from family members, friends, and the general public on their career choice, negatively affects their decision to pursue their career [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who spend more time (more than a month) doing their psychiatry ward rotation are more likely to develop interest in mental health than those who spend less time (not more than a month or no psychiatry rotation) [12]. A greater knowledge of mental health, better perception of job prospects in psychiatric nursing than other fields, and having a positive attitude towards psychiatry are also linked to choosing a career in mental health nursing [14,15]. Apart from the direct influence of stigma towards people with mental illness, the exposure of students considering a career in mental health to stigmatizing comments from family members, friends, and the general public on their career choice, negatively affects their decision to pursue their career [16].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the direct influence of stigma towards people with mental illness, the exposure of students considering a career in mental health to stigmatizing comments from family members, friends, and the general public on their career choice, negatively affects their decision to pursue their career [16]. Moreover, while having a mental health condition and a family history of psychiatric illness are associated with a greater likelihood of considering a career in mental health, the difficult working environment in psychiatry is associated with a less career interest in this area [12,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Selection of the subject for a better career of a student is a vital task since it is concerned with future employment which influences the whole life of the student and ultimately leads to social development. It is a delegate decision for the students as they are ambitious about it (Batool et al, 2020, Van Dinh et al, 2019, Pratiwi et al, 2020, McKenzie et al, 2020, Wang et al, 2020, Babajide et al, 2020, Orewere et al, 2020. Some students are in confusion or careless to choose a stream.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the environmental factors, few other factors are also there. The study of 502 students showed that the different factors like self-efficacy, outcome expectation and career intention have more impact on career choice (Pratiwi et al, 2020, McKenzie et al, 2020. A survey on student mentioned in (Madden et al, 2018) specified that hardness and softness of a subject do not matter for a student if he/she has an interest in that subject.…”
Section: Introductionmentioning
confidence: 99%
“…Retained educators who do not receive regular wage and whose working hours were reduced on account of the adoption of flexible work arrangements including reduction of work hours or work days, rotation of workers, forced leave, etc. by their employers, resulting in reduced income (MacKenzie, 2020). According to Philippine Statistics Authority (2020), among the employed persons in educator sector who were not at work, the majority (97.0%) expressed that their reason for not being at work was due to the COVID-19 pandemic, and community quarantine.…”
Section: Introductionmentioning
confidence: 99%